A capacitive angular sensor with flexible digitated electrodes. Issue 4 (26th August 2014) - Krklješ, Damir; Vasiljević, Dragana; Stojanović, Goran
Abstract : Purpose: – This paper aims to present a prototype of a capacitive angular-position sensor which exploits advantages of flexible/printed electronics. The novelty of the sensor is that the capacitor structure is placed at the circumference of the rotor and stator, that it posses two channels (capacitor structures) electrically shifted for p/4 and that the rotor is common for both channels. The electrodes of the sensing capacitor are digitated, providing a triangular transfer function. Design/methodology/approach: – This sensor prototype consists of two flexible inkjet-printed silver electrodes forming a cylindrical capacitor structure. One of them is wrapped around the stator and another is wrapped around the rotor part of a simple mechanical platform used to precisely adjust the angular displacement. Findings: – The capacitance as a function of angular position was measured using an inductance capacitance impedance (LCZ) Meter, and results are presented for a full-turn measurement range. The experimental results are compared with analytical ones and very good agreement has been achieved. Originality/value: – The proposed capacitive sensor structure can be used as an absolute or an incremental encoder with different resolutions, and it can be applied in automotive industry or robotics.